FAMILY CONOPIDAE - Rocha, Leonardo Silvestre Gomes; Mello-Patiu, Cátia Antunes De (Zootaxa, 2016)
A catalogue of the Conopidae known from Colombia, with 16 species distributed in four genera, is presented. The richest group is Stylogaster Macquart. Geographic distributions are given for each species.